2017
DOI: 10.1177/1558944717695747
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Clinical Assessment of Intramedullary Nail Fixation for the Treatment of Unstable Metacarpal Fractures

Abstract: We found that this technique allowed for the stabilization of fractures, early ROM, resumption of usual activities, reduced immobilization, and minimal complications. A removable orthosis, instead of a cast, allowed for earlier mobilization of the wrist, metacarpophalangeal, and proximal interphalangeal joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Understanding the underlying anatomy of metacarpals is essential for surgical fixation and reconstruction (Rivlin et al, 2015). Metacarpal fractures lead to shortening of metacarpal length, with intramedullary nailing (IMN) reported to restore metacarpal length (Mirza et al, 2018). Our data reveals further information with use of radiographic imaging regarding metacarpal dimensions of length, neck width, narrowest body width, and narrowest medullary canal width.…”
Section: Discussionmentioning
confidence: 76%
“…Understanding the underlying anatomy of metacarpals is essential for surgical fixation and reconstruction (Rivlin et al, 2015). Metacarpal fractures lead to shortening of metacarpal length, with intramedullary nailing (IMN) reported to restore metacarpal length (Mirza et al, 2018). Our data reveals further information with use of radiographic imaging regarding metacarpal dimensions of length, neck width, narrowest body width, and narrowest medullary canal width.…”
Section: Discussionmentioning
confidence: 76%
“…11,12 In addition, it allows for the use of a single nail, compared with unlocked nails that required multiple nails to fixate one fracture. 12 When using this technique, Mirza et al 7 found a 10% complication rate of IM Nail backing out, tendon irritation, and one case of a tendon rupture. 7 These complications required either revision or nail removal.…”
mentioning
confidence: 99%
“…12 When using this technique, Mirza et al 7 found a 10% complication rate of IM Nail backing out, tendon irritation, and one case of a tendon rupture. 7 These complications required either revision or nail removal. 7 Mirza et al also reported that patients commonly reported experiencing postoperative prominence and swelling near the base of the metacarpal.…”
mentioning
confidence: 99%
See 2 more Smart Citations